DETERMINANT ANALYSIS OF JOB SATISFACTION ON HOSPITAL’S EMPLOYEE PERFORMANCE - Harahap, Sabasdin; Andry, Andry; Kusumapradja, Rokiah (Fakultas Ilmu Kesehatan Universitas Gresik, 2022)
Productivity and hospital quality service depend on the hospital's ability to manage its human resources. Job satisfaction reflects the feeling of the worker shown in their attitude towards work and their working environment. Dissatisfied employees tend to have poor performance and affected hospital performance, such as decreasing Bed Occupancy Rate (BOR) or increasing turnover employee numbers. The purpose of this study is to identify the determinant factors of job satisfaction towards employee’s performance. This Cross-sectional study was done at RS MB, Tulang Bawang, Lampung in December 2019-February 2020 with a total sampling method. Data collection using questionnaires regarding determinant factors of job satisfaction towards employee’s performance. The factors analyzed were co-workers, relationship with superiors, work itself, salaries, career patterns. Data analysis using multiple linear regressions. The result was that job satisfaction influenced employee performance. Factors determinant of job satisfaction towards employee performance was work it-self.